Comparison of Neck Circumference to Thyromental Distance as A Predictor of Difficulty Visualizing The Larynx in Elective Surgery Patients At Haji Adam Malik General Hospital - Adzim, Teuku Fauzan; Winata, Ade; Irina, Rr Sinta (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Airway management is the responsibility of anesthesiologists, but clinical assessment documentation is often incomplete. Difficult laryngoscopy and intubation occur in 1% to 15% of cases. Intubation is considered difficult if it takes more than ten minutes for a trained anesthesiologist to achieve successful endotracheal intubation. In Indonesia, difficult laryngeal visualization occurs in 10.1% of Malay patients. Common predictors include Mallampati classification, thyromental distance (TMD), obstructive sleep apnea (OSA), male gender, and age.Objective: This study aims to compare neck circumference (NC) to TMD as a predictor of difficulty visualizing the larynx.Methods: This diagnostic study aimed to evaluate the sensitivity and specificity of NC and TMD as predictors of difficult laryngeal visualization in patients undergoing elective surgery at Haji Adam Malik General Hospital, Medan. The sample consisted of 85 patients, aged 18 years or older, with ASA classifications of 1-2, who were undergoing general anesthesia. Exclusion criteria included limited mouth opening, acute burns, airway tumors, or anatomical abnormalities.Result: The mean age of participants was 54.97 ± 14.41 years, with a mean body mass index (BMI) of 26.63 ± 3.12 kg/m², and an average NC/TMD ratio of 6.37 ± 0.87. Patients with an NC/TMD ratio > 5 had difficult intubation in 87.5% of cases, while those with an NC/TMD ratio < 5 had easy intubation in 94.6% of cases. Fisher's Exact test showed a significant association (p < 0.001). The NC/TMD ratio had a sensitivity of 95.45%, specificity of 85.36%, positive predictive value (PPV) of 87.5%, negative predictive value (NPV) of 94%, and an area under the curve (AUC) of 90%.Conclusion: The NC/TMD ratio is a significant and accurate predictor of difficult intubation, supporting its use as a simple, non-invasive preoperative tool.